Characterization of two new zinc(II) complexes with saccharinate and imidazole or benzimidazole as ligands - Williams, Patricia Ana María (2004)
The crystal structure of the complexes [Zn(sac)₂(im)₂] (1) and [Zn(sac)₂(bzim)₂]₂⋅2Et-OH⋅H₂O (2) (sac = saccharinate anion; im = imidazole; bzim = benzimidazole; EtOH = ethanol) was determined by single crystal X-ray diffractometry. Complex 1 crystallizes in the monoclinic P2₁/n space group with a = 9.1585(5), b = 16.4409(6), c = 15.0249(5) Å, β = 94.079(1)°, and Z = 4, whereas complex 2 belongs to the triclinic space group P1 with a = 10.8500(2), b = 12.4860(2), c = 13.5640(3) Å, α = 115,696(1), β = 100.086(1), γ = 102.169(1)°, and Z = 1. In both complexes, the Zn(II) cations are in a slightly distorted tetrahedral ZnN₄ environment, coordinated to two saccharinate anions and to two imidazole (1) and to two benzimidazole (2) molecules. The complexes were also characterized by means of infrared spectroscopy and their thermal behavior investigated by means of thermogravimetric and differential thermal analytical techniques.